HEALTH ASSESSMENT SKILLS OF NURSING STUDENTS: DESCRIPTIVES STUDIES - Halimatusyadiah; Hasbyalloh, Mochamad Salman; Wulan Hardian, Ratna; Putri Septiawati, Adinda (STIKes Budi Luhur Cimahi, 2024)
The integrated clinical practicum equips prospective nursing students with the essential skills required to operate effectively as healthcare professionals who will transition into physicians following licensure. The population of nursing students at STIKes Budi Luhur Cimahi is 632 students. The sample was 244 students with cluster random sampling techniques, 36 nurses, 148 nursing S1 students, and 60 nursing D3 students. Data analysis used chi square and kolmogorov Smirnov tests. Based on the results of P-Value 1.00 with the age of 18-20 years with a total frequency of 18 with skilled skills of eight twenty-two points two percent (22.2%), ages 21-23 years with a total frequency of 30 with skilled skills of twenty point four percent (20.4%) and ages 24-26 years with a total frequency of 5 with skilled skills of twenty-one point seven percent (21.7%). Regarding gender, based on the results of P-Value 0.244 with male gender with a total frequency of 73, sixteen point four percent (16.4) were obtained. And the female gender with a total of twenty-one point seven percent (27.1%) is skilled. In acquiring health assessment skills while in the undergraduate program, nurse educators must consider the variables of age profile, gender, and type of student. Hence, it is imperative for nurse educators to cultivate diverse pedagogical approaches in order to cater to the varying requirements of diverse student populations. Keywords: Age, Gender, Skills, Nursing